The role of great power war in the rise of Hegemons : a study of Dutch Hegemonic ascent in the modern world-system - Siebrits, Andre (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.